A SNaPshot of next generation sequencing for forensic SNP analysis. (January 2015) - Daniel, R.; Santos, C.; Phillips, C.; Fondevila, M.; van Oorschot, R.A.H.; Carracedo, Á.; Lareu, M.V.; McNevin, D.
Highlights: Pooled PCR amplicons from five forensic SNaPshot assays were applied to Ion Torrent. Approximately 72 Mb of sequence was generated from two 10 Mb Ion 314™ v1 chips. 136 unique SNPs were accurately genotyped from 0.1 to 0.3 ng template DNA. High concordance (97%) was observed between Ion Torrent and SNaPshot genotypes. Sanger sequencing confirmed a further 1.5% of genotypes discordant with SNaPshot. Abstract: Forensic phenotyping can provide useful intelligence regarding the biogeographical ancestry (BGA) and externally visible characteristics (EVCs) of the donor of an evidentiary sample. Currently, single nucleotide polymorphism (SNP) based inference of BGA and EVCs is performed most commonly using SNaPshot ®, a single base extension (SBE) assay. However, a single SNaPshot multiplex PCR is limited to 30–40 SNPs. Next generation sequencing (NGS) offers the potential to genotype hundreds to thousands of SNPs from multiple samples in a single experimental run. The PCR multiplexes from five SNaPshot assays (SNP for ID 52plex, SNP for ID 34plex, Eurasiaplex, IrisPlex and an unpublished BGA assay) were applied to three different DNA template amounts (0.1, 0.2 and 0.3 ng) in three samples (9947A and 007 control DNAs and a male donor). The pooled PCR amplicons containing 136 unique SNPs were sequenced using Life Technologies' Ion Torrent™ PGM system. Approximately 72 Mb of sequence was generated from two 10 Mb Ion 314™ v1 chips. Accurate genotypes were readily obtained from all three template amounts. Of a total of 408 genotypes, 395 (97%) were fully concordant with SNaPshot across all three template amounts. Of those genotypes discordant with SNaPshot, six Ion Torrent sequences (1.5%) were fully concordant with Sanger sequencing across the three template amounts. Seven SNPs (1.7%) were either discordant between template amounts or discordant with Sanger sequencing. Sequence coverage observed in the negative control, and, allele coverage variation for heterozygous genotypes highlights the need to establish a threshold for background levels of sequence output and heterozygous balance. This preliminary study of the Ion Torrent PGM system has demonstrated considerable potential for use in forensic DNA analyses as a low to medium throughput NGS platform using established SNaPshot assays.